Process improvement in access management to increase database visibility - Nievera, Zandrea Klair D. (Animo Repository, 2023)
Digitalization has been over the place in the past years which accelerated when the pandemic hit worldwide. Although there is a slow uptake of digitalization in the country, it is quite a different story for the banking industry. Even prior to the pandemic, banks have been developing strategies involving digital initiatives. In this changing times, digital technologies can help in keeping the business operational and perform processes efficiently and effectively. However, the implementation of these strategies is not a walk in the park. There is also a fair share of issues arising when the strategies are not properly executed. The purpose of this action research is to address the need to increase database visibility through proper access management. With the use of the different co-inquiry tools, my collaborators and I have established that the adoption of digitalization in the department was not foolproof such that at some point, not all the required users were given access to the database after the shift to the cloud-based infrastructure. We were able to recognize the forces driving and restricting change and with the use of McKinsey’s 7 framework, we identified that there is misalignment in the system, structure, staffing, and skills contributing to the issue on database visibility. Anchored in the concept of internal control, authenticate, authorize, and audit (AAA) model, and identity and access management, we were able to devise a tailored-fit approach wherein the interventions involved proper group ID tagging through the group administrators and the periodic granting of access to the main library. The simultaneous application of the interventions resulted in the gradual improvement and achievement of the desired outcomes in terms of increasing database visibility, having clear roles and responsibilities, and encouraging people to use the database (higher database usage).